ETHICAL DILEMMAS OF NEWSPAPER ORGANISATIONS AND THE USAGE OF SOCIAL MEDIA FOR JOURNALISTS IN LAGOS STATE - Rasheed, Buhari Olaoluwa; Bernice, Adeleye Demilade (Universitas Islam Negeri Mataram, 2025)
This study examines the ethical dilemmas and the use of social media as a source of information owned by journalists. The research used mixed methods (quantitative and qualitative). The study involved 81 journalists and 3 editors from three selected newspaper organizations in Lagos State. Using questionnaires and interview guides, data were collected and analyzed with the Statistical Package for Social Science (SPSS). Results show that specific dilemmas include verification of credibility, privacy concerns, unbalanced information, balancing transparency, and maintaining individual privacy rights. Verifying information from credible social media accounts helps to increase actual and accurate reporting. Using images and videos can corroborate information, as well as using fact verification tools and plugins.